A multi-agent protocol for service level agreement negotiation in cloud federations. (2016) - Messina, Fabrizio; Pappalardo, Giuseppe; Santoro, Corrado; Rosaci, Domenico; Sarné, Giuseppe M.L.
The emergence of complex cloud services and the growing number of QoS metrics entail the need of automation to transform business requirements into QoS constraints. Furthermore, in the emergent context of Cloud Federations providers need to share knowledge to improve interoperability when negotiating SLA (Service Level Agreements). Intelligent software agents are capable of supporting activities related to SLA negotiation, as well as sharing knowledge into large-scale distributed environments. Since they are usually provided with different ontologies, understanding the meaning of the messages requires the availability of common, global ontologies among customers and providers. In order to deal with this issue, we discuss a multi-agent SLA negotiation protocol which does not need a common global agent ontology. The protocol takes into account different concerns related to the understanding of semantic and technical terms, and the knowledge about the agent abilities on semantic and technical terms are shared among the Cloud Federation.